PEMBELAJARAN KOOPERATIF TIPE STUDENT TEAMS ACHIEVEMENT DIVISION (STAD) UNTUK MATERI GEOMETRI PADA SISWA KELAS X SMAK ST. PETRUS ENDE - Yuliana Bebhe Folo (JUPIKA: JURNAL PENDIDIKAN MATEMATIKA, 2019)
The formulation of the problem in this research is "how the students activity in following the learning of mathematics by using STAD type cooperative learning model of geometry material on the students of class X SMAK ST.Petrus Ende and how STAD type cooperative learning model can improve the result of learning mathematics material Geometry in grade X students SMAK ST Petrus Ende. With the aim of this research is to know the result of learning mathematics of Geometry material by applying STAD type cooperative learning model in STP X class student ST Peter Ende and to know student activity in following learning mathematics of geometry material at student of class X SMAK ST.Petrus Ende. The type of this research is Classroom Action Research with approach done is qualitative approach supported by approach of signifikanitatif. Population in this research is student of class X SMAK ST. Peter Ende, the sample used in the study were students of class X3 with the number of students 19 people. Data collection techniques used in this study is the method of observation, interview methods and learning methods. Based on the results of the analysis and discussion, it is found that: (1) the implementation of cooperative learning model of Student Teams Achievement Division in Mathematics learning at SMAK ST. Peter Ende is a very good thing in improving students' learning outcomes, especially if the Student Teams Achievement Division's cooperative learning model is applied in accordance with the STAD model steps, (2) the students are actively involved in the learning activities and can work on the THB problem with Good and get a satisfactory presentation. This can be seen from the increase in the percentage of student learning outcomes with mastery of the class. In the first cycle, the percentage of completeness reached 26.31% with the level of learning outcomes in the category enough, and in the second cycle increased to 100% with very good category